PERAN EFIKASI DIRI GURU DALAM PENDIDIKAN ANAK USIA DINI - Wiraadi Tria Ariani Nyoman (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
Early Childhood Education is an early education that facilitates children to get the right stimulation, guidance, nurturing, and learning so that the child's abilities and skills can develop optimally. Teachers play a role in stimulating the quality care and education that early childhood needs. When the teacher provides education and develops the character of the child, the teacher needs confidence in his or her abilities called self-efficacy. Self-efficacy refers to an individual's belief that he is capable of performing tasks, in this case the higher his or her efficacy the more confident or confident he is able to achieve success. This research method is a literature study that examines scientific literature related to the role of teacher efficacy in Early Childhood Education. Based on literature studies, teacher self-efficacy can be used to develop teacher innovation behavior in their work. Teachers with higher self-efficacy showed a higher level of innovation behavior. By building the teacher's self-efficacy, it will affect the teacher's confidence when doing teaching objectives, preparing teaching materials, class interaction patterns, roles, classroom practices and others.